Simulation study of the effect of fasteners on the attenuation of orbital ultrasonic guided waves - Mingqiang Wang (PLoS ONE, 2026)
Ultrasonic guided wave technology offers advantages such as long-distance propagation and full-section detection for non-destructive testing of rails. However, operational rails are typically limited by fastener systems, resulting in increased guided wave energy attenuation and shorter propagation distances compared to free rails. Therefore, studying the mechanism by which fasteners influence guided wave attenuation is crucial. This paper presents a comprehensive three-dimensional solid fastener-rail contact mechanics and transient dynamics coupling model that considers the static action and complex contact relationship between fasteners and rails. The model uses an implicit-explicit combination method to simulate the propagation of guided waves in operational rails. This paper presents a simulation in which a preload force of 20 kN was applied to the fasteners, and the stress distribution of the model was analyzed. A transient analysis of the guided wave was performed under the preload force to investigate the influence of fasteners on guided wave attenuation in rails by comparing attenuation with and without fasteners. Additionally, this paper explores the impact of two contact types, penalty and motion, on wave attenuation in Abaqus/Explicit. The results demonstrate that fasteners significantly exacerbate wave attenuation in rails. The wave packet amplitude calculated using the penalty contact form is slightly greater than that calculated using the motion contact form, and this difference increases with propagation distance.